Fitness-to-work considerations in the paradigmatic pain condition of headache disorder - Xiangning Fan; Ellina Lytvyak; Charl Els; Sebastian Straube (The Journal of Headache and Pain)
Abstract Headache disorders are common, including in the working population. Clinicians caring for patients with headache need to be aware of work-related factors as potential causes or triggers of headache disorders, and consider the impact of headache on fitness-to-work, especially in safety-sensitive and decision-critical roles. Such fitness-to-work determination should include individualized consideration of the nature of the headache disorder itself, the pattern of the headache, the impact of sleep deprivation on the headache as it relates to fitness to do shiftwork, medication and substance side effects, fitness-to-work implications of associated medical or psychiatric conditions, and the potential of symptom feigning or malingering for secondary gain. As clinicians often struggle with fitness-to-work determinations, a structured approach to fitness-to-work assessments in headache conditions and other pain conditions would improve clarity for clinicians and increase the quality of care provided to patients, with potential benefits for workplace safety and policy in this arena as well.